Dynamic testing and numerical modelling of a pedestrian timber bridge at different construction stages. (15th March 2023) - Bergenudd, Jens; Battini, Jean-Marc; Crocetti, Roberto; Pacoste, Costin
Abstract: This article studies the dynamic properties of a single span pedestrian timber bridge by in-situ testing and numerical modelling. The in-situ dynamic tests are performed at four different construction stages: (1) on only the timber structure, (2) on the timber structure with the railings, (3) on the timber structure with railings and an asphalt layer during warm conditions and (4) same as stage 3 but during cold conditions. Finite element models for the four construction stages are thereafter implemented and calibrated against the experimental results. The purpose of the study is to better understand how the different parts of the bridge contribute to the overall dynamic properties. The finite element analysis at stage 1 shows that longitudinal springs must be introduced at the supports of the bridge to get accurate results. The experimental results at stage 2 show that the railings contributes to 10% of both the stiffness and mass of the bridge. A shell model of the railings is implemented and calibrated in order to fit with the experimental results. The resonance frequencies decrease with 10–20% at stage 3 compared to stage 2. At stage 3 it is sufficient to introduce the asphalt as an additional mass in the finite element model. For that, a shell layer with surface elements is the best approach. The resonance frequencies increase with 15–30% between warm (stage 3) and cold conditions (stage 4). The stiffness of the asphalt therefore needs to be considered at stage 4. The continuity of the asphalt layer could also increase the overall stiffness of the bridge. The damping ratios increase at all construction stages. They are around 2% at warm conditions and around 2.5% at cold conditions for the finished bridge. Highlights: Longitudinal springs are required at the bridge supports to match the experiments. The railings increase the stiffness and mass of the bridge equally much. The asphalt is mainly an added mass at warm conditions (40 °C). The stiffness of the asphalt must be considered at cold conditions (0 °C).